Management of the field of studies “Estudios Culturales Latinoamericanos” (ECL) - Pulido Tirado, Genara (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
The Cultural Studies, born in Birmingham in the sixties, have spread to the most diverse latitudes. The Cultural Studies that is done in Latin America or made by Latin American authors located in North American universities are those that maintain and adapt the original spirit of this field of study that in other places is highly contaminated by the neoliberal ideology. In this article we trace the coordinates on which the Latin American Cultural Studies are based, as well as the bases that sustain them. Theorisation and practice can not take place apart from the knowledge of a history in which the publication of emblematic collective volumes and the debates that take place around congresses and scientific meetings that take place as of 1990, at the same time as writing, stand out the history of another form of knowledge production according to some countries in which criticism and cultural theory have a long tradition.